PROFIL KOMPETENSI SISWA SMP DI JAWA TIMUR DALAM MENYELESAIKAN TES BERFIKIR TINGKAT TINGGI PEMBELAJARAN SAINS - Hasan Subekti (UNIVERSITAS PGRI MADIUN, 2014)
Familiarize learners to communicate, think critically and creatively and to consider moral values of Pancasila is one Permendikbud 81 A mandate in 2013. The need for students to be exposed to high level thinking tests in Learning Science is to hone the skills of students at the high school level. The purpose of this study was to describe the level of student mastery and achievement test indicator junior high school students in East Java in resolving high level thinking tests of learning science. This study was conducted at 20, 23, and 28 November 2012 in three districts, there are: Blitar, Mojokerto, and Pamekasan. The population of this study were junior high school students in East Java with a sample of students SMP 3 Nglegok Blitar (15 peoples), SMP 2 Dlanggu Mojokerto (15 peoples) and SMP 7 Pamekasan (15 peoples) by using purposive sampling technique. Data sources such as student scores on the analysis of high-level thinking skills test developed by USAID Priority Team. Techniques of data collection conducted by researchers through the provision of test instruments to students, then corrected degree of truth answers based on predefined criteria. Analysis of data in quantitative descriptive data then qualitatived. The conclusions of this study are: competence Junior high school students in East Java in resolving high level thinking tests category learning science enough (enough with a mean value of C- with a score of 43.8) and achievement test results categorized good indicators, namely: (a) observation of characteristic Distinctive animals (75.6), and analyze the properties of liquid water (75.6).